IMPROVING CHILDREN’S LANGUAGE DEVELOPMENT THOUGH IMAGE MEDIA IN 21 ST CENTURY LEARNING IN TK NEGERI MODEL TERPADU MADANI PALU - Anitasari, Ni Putu; Ermayanti, Ni Gusti Ayu Putu; Dyantari, Putu (STAH Dharma Sentana Sulawesi Tengah, 2023)
Based on the results of observations of the problems found in the field, children's language development is still lacking due to the ineffective use of media in learning. The formulation of the problem in this study is how to improve children's language development and how the obstacles faced by teachers improve children's language development through the media of images in 21st century learning in the Madani Integrated Model Public Kindergarten in Palu. The research aims to describe how to improve children's language development and the obstacles faced by teachers in improving children's language development through the media of images in 21st century learning in the Integrated Madani Model Public Kindergarten in Palu. Research using descriptive qualitative. The results of the research are first, finding ways to improve children's language development through the media of images in 21st century learning. Ways to improve children's language development are repeated learning, learning while conversing about the pictures shown, inviting them to interact while looking at the pictures and telling stories about what shown learning while playing. The two obstacles faced by the teacher are: 1) Facilities and infrastructure, 2) the character of the children is different, 3) the children are silent when asked by the teacher, and 4) there are also children who are too engrossed to want to continue playing, telling stories and disturbing their friends while studying.